Development of Multi-Channel Seismic–Electrical Combined Rolling Coverage Measurement System - Zucan Lin; Qisheng Zhang; Keyu Zhou (Applied Sciences)
Electrical and seismic exploration are two widely used geophysical methods in geological surveys. They reflect different geophysical properties of underground rocks, but each method can only provide information from a single perspective of the rock structure’s physical parameters. As a result, relying on a single geophysical method can lead to ambiguous interpretations. To address this issue, this paper presents the development of a multi-functional, high-power, multi-channel, rolling, fast measurement system for combined electrical and seismic exploration. The system features the following capabilities: it can be used simultaneously for both electrical and seismic exploration; it supports high-power operation, with a transmission power of up to 10 kW during electrical exploration; it includes multiple measurement channels for rolling measurement and data acquisition, with a sampling rate of up to 100 ksps, significantly improving work efficiency and expanding the frequency range. The distance between channels can be selected from 1 to 20 m, greatly enhancing the system’s adaptability to various environments. Additionally, we have designed accompanying upper-level software that not only stores data internally but also displays waveforms in real-time on a computer for monitoring and control. The experimental results demonstrate that the instrument operates stably and meets the requirements for field exploration.